Lattice Dynamics of Face Centred Cubic Crystals - Yusra A. Sade; Garba Babaji (Archives of Current Research International, 2018)
Lattice dynamics of fcc metal crystals have been studied within the harmonic approximation. Phonon dispersion relation (frequency as a function of wave vector) along the symmetry directions [100], [110] and [111], density of states and the heat capacity have been calculated for Aluminum, Copper and Lead using lattice dynamics model debye. The results obtained were compared with results from neutron scattering experiment. The calculated results of phonon dispersion relations as well as the heat capacities are generally in good agreement with the experimental results.